JURASSIC WORLD : FROM DNA TO INDOMINUS REX! - Rowlands, Caroline (Children's book writer) (Selangor, Malaysia : Orbit Buku Sdn. Bhd, 2017)
An augmented reality book which provides information about dinosaurs from the Jurassic World movie and allows the dinosaurs to "come to life" on your mobile device screen.
"With extra augmented reality Jurassic experiences"--Cover.
"Powered by Digital Magic"--Cover.
Text and illustrations on endpapers.
Interactive software for this book (iCarltonAR) is available for free as a separate download from the iTunes store or Google play. System requirements: iPhone 5s and above, iPad 4 and above, or iPod touch 6th Generation or above with iOS9 and above ; Android devices using Android 4.0 and above with ARMv7 NEON processors ; INTEL ATOM based devices are not fully supported. Dual user mode will require an active wi-fi connection.
Keywords: Jurassic Park (Motion picture) -- Juvenile literature; Jurassic World (Motion picture) -- Juvenile literature; Dinosaurs -- Juvenile literature; Interactive multimedia